Tom Jones [videorecording (DVD)] - Hughes, Gwyneth; McLeod, Solly; Wilde, Sophie; Duvitski, Janine; Fallon, Lucy, 1995-; Fielding, Susannah, 1985-; Fleet, James; Kelly, Dean Lennox; Mackie, Pearl, 1987-; Merchant, Tamzin; Montagu, Felicity, 1960-; Rhind-Tutt, Julian, 1968-; et al. (PBS, 2023)
Abandoned as a baby, rescued and adopted by a country gentleman, Tom Jones grows up kind, handsome, free-spirited, and very popular with the ladies. But he cannot escape his lowly birth. When he falls in love with the bright, beautiful heiress Sophia Western, and she falls in love with him, their families unite against the match. They both end up in London, facing the wiles and whims of Sophia's aunt, the beguiling but dangerous Lady Bellaston, who will stop at nothing to destroy their love. Can Tom ever convince Sophia that he can be true to her? In this classic romantic comedy based on Henry Fielding's novel, can love conquer all?